Efeito da adição de clorexidina nas propriedades adesiva e antibacteriana de um cimento de ionômero de vidro de alta viscosidade - Becci, Ana Carolina de Oliveira [UNESP] (2013)
The aim of this study was to evaluate the bond strength to dentin and the microbial composition of the biofilm formed over a high-viscosity GIC to which chlorhexidine diacetate (CHX) was added at different concentrations. CHX was mixed with GIC powder at 0.5%, 1% and 2% (w/w). GIC without CHX was used as control. In the first study, eighty human third molars were used. They had an area of dentin exposed on the occlusal surface. Half of the specimens were kept sound and the other half was subjected to artificial caries induction. In each dentin surface a cylindrical specimen with 1 mm in diameter and 1 mm in weight (n=10 per group) was made. They were kept at 37°C and 100% humidity for 24 hours and tested for microshear. The results were analyzed using Kruskal-Wallis and Mann Whitney tests (α = 0.05). In the second study, volunteers (n=8) wore palatal appliances containing specimens with 4mm in diameter and 1mm in weight. The material with increasing concentrations of chlorhexidine were tested by all volunteers for a period of 7 days each, with a wasout period of 15 days. After each step, the biofilm formed on the specimens were collected and analyzed. Data from total anaerobic microorganisms, total streptococci, mutans streptococci and lactobacilli were analyzed by repeated measures ANOVA followed by Tukey test. The significance level was set at 5%. There were no statistical significant differences between bond strength of sound and caries-affected dentin (p> 0.05). Groups GIC, GIC+CHX 0.5% and GIC+CHX 1% showed bond strength statistically similar (p> 0.05) and higher than GIC+CHX 2% group (p ≤ 0.025). Microbial counts showed statistical significant differences among groups only for lactobacilli (p<0.05). GIC+CHX 2% presented higher mean counts than GIC and GIC + CHX 0.5% (p<0.05). In conclusion, the addition of CHX diacetate 0.5% and 1% did not change bond strength of a high-viscosity GIC in...